(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article proposes, based on the analysis of dramaturgy – Macacos and Makunaimã. O mito através do tempo – to debate the decolonial turn in Brazilian theater. I start from the hypothesis that the artistic questioning of the country’s political reality in its recent confrontations - threat of a military coup in the Bolsonaro Government, censorship of countless artistic works in the period, loss of thousands of lives due to the Covid-19 pandemic - contributed to the problematization and, consequently, growth of identity themes in opposition to repression, far-right conservatism and the fight for equal rights and social justice.